Europe Entrapped. Issue 5 (12th August 2013) - Offe, Claus
Abstract The EU in 2013 finds itself at the crossroads of either something considerably better or something much worse than the status quo; in other words, in a crisis. That much is nearly universally understood, both within Europe and widely beyond. So I am certainly not alone in believing that the current crisis, a crisis that is the cumulative outcome of a financial market, sovereign debt and EU integration/democratic deficit crises, is an extremely serious and unprecedented one, frightening due to its complexity and uncertainty. If it cannot soon be resolved (but nobody knows how soon is 'soon enough') through a major institutional overhaul of the EU, both the political project of European integration and the global economy will suffer badly—to say nothing about the massive social suffering it has caused already in the countries of the European periphery.